The Use of BOST Method as a Tool to Standardize Tasks in Hot Dip Galvanizing Process Improvement - Sygut, Piotr; Klimecka-Tatar, Dorota; Ingaldi, Manuela; Borkowski, Stanisław (Manufacturing Technology Journal, 2016)
Standardization is the basis for improvement in the company. This allows for repeatability performance of activities and thus the stability of the process. This chapter presents the standardization as part of Toyota's production system. Standardization is also one of the elements examined using the method BOST, because it was used for hot dip galvanizing process improvement. The research was carried out in one of the national companies producing steel products and providing services in the field of modern anti-corrosion protection, in particular hot-dip galvanizing.
Keywords: hot-dip galvanizing; BOST method; improvement of production processes